Odpowiedzi

Najlepsza Odpowiedź!
2009-11-08T17:14:39+01:00
X²+8x+16 = x+x+8x+16=10x+16
36-49x² =36-49×x²=49x²-36=49+x+x-36=5x²
4x²-4x²+1 =4×x²-4×x²+1=1
64x³-27 =64×x×x×x-27=37x³
x²-12x+36 =36+(-10x)=36-10x=26x
25-9x²=25-9×x×x=16x²
x⁴+2x²+1 =2x(do potegi 6)+1=3x(do potegi 6)
a²-14a+49 =13a+49= 62a
4+81a =85a
x⁴+6x²+9 =6x(do potegi 6) + 9= 16x(do potęgi 6)
(3x+4)²=3x²+4²=3×x²+16=19x²
(4a-2)³=4a³-2³=4a³-8=-4a³
(5x-3)²=5x²-3²=5x²-9=-14x²
(2a+3)³=2a³+27=29a³


mam nadzieje ze sie nie pomyliłam:D ;))
2009-11-08T18:03:45+01:00
X²+8x+16 =(x+4)^2
36-49x² =(6-7x)(6+7x)
4x²-4x²+1 =1
64x³-27 =(4x-3)(16x2+12x+9)
x²-12x+36 =(x-6)^2
25-9x²=(5-3x)(5+3x)
x⁴+2x²+1 =,,,,,
a²-14a+49 =(a-7)^2
4+81a =,,,,,,
x⁴+6x²+9 =,,,,
(3x+4)²=9x2+24x+16
(4a-2)³=64a3-96x2+48x-8
(5x-3)²=25x2-30x+9